2017
DOI: 10.7554/elife.30552
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the veil on the dynamics of neuronal activities evoked by transcranial magnetic stimulation

Abstract: Transcranial magnetic stimulation (TMS) is a widely used non-invasive tool to study and modulate human brain functions. However, TMS-evoked activity of individual neurons has remained largely inaccessible due to the large TMS-induced electromagnetic fields. Here, we present a general method providing direct in vivo electrophysiological access to TMS-evoked neuronal activity 0.8–1 ms after TMS onset. We translated human single-pulse TMS to rodents and unveiled time-grained evoked activities of motor cortex laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 65 publications
7
63
1
Order By: Relevance
“…As decay constant increases, the silent period also increases. This agrees with experimental results, but overall the modeled CSP is somewhat longer than typical measured CSPs [24]. The CSP reflects the long period in which the layer 5 pulse rate ( Fig.…”
Section: Paired-pulse Protocolssupporting
confidence: 89%
See 2 more Smart Citations
“…As decay constant increases, the silent period also increases. This agrees with experimental results, but overall the modeled CSP is somewhat longer than typical measured CSPs [24]. The CSP reflects the long period in which the layer 5 pulse rate ( Fig.…”
Section: Paired-pulse Protocolssupporting
confidence: 89%
“…2(b) shows mean activity across a population, the peaks and troughs of the plot should not be considered as the I-waves per se; rather we may expect such waves to be possible during the times where the activity is large. Changes in layer 5 firing rate are consistent with recent invasive recordings in rodents [24] and non-human primates [38].…”
Section: Motor Evoked Potential At Restsupporting
confidence: 87%
See 1 more Smart Citation
“…The loss of EEG signal for up to 15 ms after the TMS pulse therefore represents a limitation of our study. We cannot exclude that significant changes in TMS-evoked or induced EEG responses have occurred in this very early time window, especially because excitation of pyramidal neurons projecting to the spinal cord and responsible for the MEP generation occurs in the very first milliseconds after the TMS pulse (Li et al 2017). This limitation could be possibly overcome in future studies using faster sampling rates and more focal coils that minimize the activation of scalp muscles and produce smaller TMS-related artifacts.…”
Section: Figure 6 Topographical Plots Of Average Teps and Results Ofmentioning
confidence: 99%
“…A large body of evidence from both human ppTMS-EMG studies [6,7,36,37] and intracellular recordings in animal [38,39] has demonstrated that a suprathreshold TMS pulse to primary motor cortex results in a period of strong net excitation lasting between 10-30 ms followed by a period of net inhibition lasting approximately 50-200 ms at the site of stimulation. However, it is unclear whether the same pattern of response is present in other methods recording the cortical response to TMS, such as EEG, as these methods are sensitive to different scales of neural activity.…”
Section: Emg and Eeg Measures Of Local Cortical Responses To Tmsmentioning
confidence: 99%